2015
DOI: 10.1038/cdd.2015.49
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte NMDA receptors' activity sustains neuronal survival through a Cdk5–Nrf2 pathway

Abstract: Neurotransmission unavoidably increases mitochondrial reactive oxygen species. However, the intrinsic antioxidant defense of neurons is weak and hence the mechanism whereby these cells are physiologically protected against oxidative damage is unknown. Here we found that the antioxidant defense of neurons is repressed owing to the continuous protein destabilization of the master antioxidant transcriptional activator, nuclear factor-erythroid 2-related factor-2 (Nrf2). By contrast, Nrf2 is highly stable in neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
157
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(172 citation statements)
references
References 56 publications
4
157
1
10
Order By: Relevance
“…Under normal unstressed conditions, Nrf2 is anchored to Keap1 and rapidly degraded (Itoh et al, 2003; McMahon, Itoh, Yamamoto, & Hayes, 2003). This process seems to be much more powerful in neurons than in astrocytes (Jimenez‐Blasco, Santofimia‐Castano, Gonzalez, Almeida, & Bolanos, 2015). Oxidative stress or exposure to electrophilic agents that react with Keap1 slow down Nrf2 degradation and lead to its nuclear accumulation.…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%
“…Under normal unstressed conditions, Nrf2 is anchored to Keap1 and rapidly degraded (Itoh et al, 2003; McMahon, Itoh, Yamamoto, & Hayes, 2003). This process seems to be much more powerful in neurons than in astrocytes (Jimenez‐Blasco, Santofimia‐Castano, Gonzalez, Almeida, & Bolanos, 2015). Oxidative stress or exposure to electrophilic agents that react with Keap1 slow down Nrf2 degradation and lead to its nuclear accumulation.…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%
“…Thus, astrocytes are equipped to protect themselves when exposed to excess reactive oxygen species (ROS) (12) and reactive nitrogen species (13,14). Moreover, astrocytes also provide nearby neurons with protective antioxidant precursors through a cell-signaling mechanism involving glutamate receptor activation by neurotransmission (11,15,16). The tight coupling between astrocytes and neurons therefore helps in energy and redox metabolism during normal brain function.…”
mentioning
confidence: 99%
“…Astrocytes provide crucial metabolic and structural support (3,4) and are key players in neurotransmission (5-7) and behavior (8). The status of many major redox couples in the brain is also regulated by astrocytes (9), through their high content of antioxidant compounds and enzymes (10) and by the constitutive stabilization of the master antioxidant transcriptional activator, nuclear factor erythroid 2-related factor 2 (Nrf2) (11). Thus, astrocytes are equipped to protect themselves when exposed to excess reactive oxygen species (ROS) (12) and reactive nitrogen species (13,14).…”
mentioning
confidence: 99%
“…In fact, this has been confirmed by different works, but with some differences in comparison with synaptic NMDAR signaling described above. Activation of PLC/PKC/ p35/Cdk5/Nrf2, a prosurvival pathway, and CAPON nuclear translocation were described in cultured astrocytes in response to NMDAR [114,126]. On the other hand, MK-801 treatment of cultured astrocytes upregulated glycogen phosphorylase and regulated the expression of growth and metabolic genes [134].…”
Section: Insights Regarding Astrocytic Nmdarmentioning
confidence: 99%
“…The same year, Jimenez-Blasco et al [126] reported that in cultured rat cortical astrocytes they observed iCa…”
mentioning
confidence: 96%